1989
DOI: 10.1161/01.cir.80.4.935
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute venous thromboembolism with low molecular weight heparin (Fragmin). Results of a double-blind randomized study.

Abstract: We performed a prospective, randomized, double-blind trial in 194 unselected patients to determine the safety and efficacy of low molecular weight heparin (Fragmin) compared with standard heparin as the initial treatment of acute venous thromboembolism. Ninety-eight patients received continuous intravenous heparin, and 96 patients received Fragmin for 5-10 days. Doses were adjusted to maintain anti-Xa levels between 0.3 and 0.6 unit/ml for patients with a high risk for a bleeding complication and between 0.4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(59 citation statements)
references
References 19 publications
3
55
0
1
Order By: Relevance
“…[17][18][19][20] We contacted the authors of the remaining 19 articles to request cancer subgroup data: One author provided us with the data 21 ; another author indicated that the data were not available anymore 22 ; we used the cancer subgroup data for 7 articles, 23-29 because they were reported in 2 published systematic reviews 5,8 ; and we were not able to obtain any outcome data for the remaining studies. [30][31][32][33][34][35][36][37][38][39] Thus, of 24 studies with cancer patients' subgroups, we were able to obtain data for 13 studies. Agreement between authors for study eligibility was excellent (kappa of 0.94).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…[17][18][19][20] We contacted the authors of the remaining 19 articles to request cancer subgroup data: One author provided us with the data 21 ; another author indicated that the data were not available anymore 22 ; we used the cancer subgroup data for 7 articles, 23-29 because they were reported in 2 published systematic reviews 5,8 ; and we were not able to obtain any outcome data for the remaining studies. [30][31][32][33][34][35][36][37][38][39] Thus, of 24 studies with cancer patients' subgroups, we were able to obtain data for 13 studies. Agreement between authors for study eligibility was excellent (kappa of 0.94).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Concomitant use of non-steroidal anti-inflammatory drugs or antiplatelet agents with LMWH is also known to increase the risk of bleeding 3 . Retroperitoneal haematoma, a severe form of bleeding which can be potentially fatal, has been reported with the use of the LMWH enoxaparin 5 and dalteparin 6 . In the case described here, spontaneous bilateral retroperitoneal haematoma developed after using the LMWH tinzaparin, to treat venous thrombosis in a patient with no known risk factors for bleeding.…”
Section: Dear Sirmentioning
confidence: 99%
“…First, the change in thrombus size was assessed by repeating venography at the end of the course of treatment [33][34][35][36][37]: LMWH were as effective as SH. Second, most studies used the occurrence of the symptomatic recurrent DVT as end-point; there was a strong trend for LMWH to be more effective and safer than SH [38][39][40][41]. Two meta-analyses of these trials found similar trends indicating improved efficacy and safety with LMWH [42,43], It is uncertain if the favorable outcomes of treatment with different LMWH can be extrapolated to ail other types of LMWH [24,42,44], Also it is not certain whether there is bioequivalence between all products.…”
Section: Low Molecular Weight Heparins (Lmwh)mentioning
confidence: 99%
“…As a consequence similar studies with different types of LMWH should be performed. Fi nally it should be noted that only a few studies used a once-daily regimen of LMWH [39,41,45], the other studies twice daily. Currently LMWH once versus twice daily are being compared.…”
Section: Low Molecular Weight Heparins (Lmwh)mentioning
confidence: 99%
See 1 more Smart Citation